Analisis Kemampuan Menulis Permulaan Fokus pada Huruf dan Kata Kelas I SD di Kecamatan Bayang Pesisir Selatan - Intan Nurani; Chandra Chandra; Inggria Kharisma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study was motivated by students' understanding of writing and completing letters and words at the early stages of learning to write. The aim is to improve students' understanding of how to write productively and descriptively. Data were collected through observation, practice questions, and documentation with a qualitative case study approach. The results showed that students were able to write loose letters, distinguish similar letters (b, d, p, q), and complete missing letters and words in the context of words and sentences.